2009
DOI: 10.4067/s0717-97072009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bath Temperature and Ph Value on Properties of Chemically Deposited Cu4sns4 Thin Films

Abstract: Thin films of Cu 4 SnS 4 semiconductors were prepared by chemical bath deposition technique in aqueous solutions. The effects of various bath temperatures (40, 50 and 60 °C) and pH values (pH 0.5, pH 1.0 and pH 1.5) on growth of films were reported. The structure and morphology characteristics of thin films of Cu 4 SnS 4 grown on indium tin oxide glass substrates were investigated by X-ray diffraction and atomic force microscopy techniques. The optical properties were measured to determine the transition type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Sadekar et al 126 deposited cubic zinc blende structures on glass substrates using triethanolamine as the complexing agent, and the band gap was found to be 2.71 eV. Kassim et al 127 prepared ZnSe thin films over ITOcoated glass substrates and found that the surface morphology of the thin films mainly depends upon the bath temperature. Lokhande et al 128 prepared ZnSe thin films on glass and FTO-coated glass substrates and found the optical band gap to be 2.9 eV.…”
Section: Review Of Some Metal Chalcogenide Thin Films Prepared By Usimentioning
confidence: 98%
“…Sadekar et al 126 deposited cubic zinc blende structures on glass substrates using triethanolamine as the complexing agent, and the band gap was found to be 2.71 eV. Kassim et al 127 prepared ZnSe thin films over ITOcoated glass substrates and found that the surface morphology of the thin films mainly depends upon the bath temperature. Lokhande et al 128 prepared ZnSe thin films on glass and FTO-coated glass substrates and found the optical band gap to be 2.9 eV.…”
Section: Review Of Some Metal Chalcogenide Thin Films Prepared By Usimentioning
confidence: 98%
“…Nowadays, there are the different techniques for fabrication ZnSe films: thermal evaporation [7], pulsed laser deposition [8], chemical bath deposition [9], spray pyrolysis [10], pulsed laser ablation [11], electrochemical deposition [12], molecular beam epitaxy [13], magnetron sputtering [14], close-spaced vacuum sublimation (CSVS) [15]. The last method due to the technical features of evaporator, allows to obtain fine-crystalline stoichiometric films in conditions approach to the thermodynamic equilibrium.…”
Section: Introductionmentioning
confidence: 99%